On the taxonomic placement of Geodromicus pusillus Coiffait, 1983 (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2012)
Luze (1903:116) described the subgenus Trichodromeus Luze, 1903 for two species of Geodromicus L. Redtenbacher, 1857. Bordoni (1984:57) identified this taxon as a separate genus. Zerche (1992:126) redescribed Trichodromeus, synonymized Neogeodromicus Bordoni, 1985 with it and proposed phylogenetic relationships of this taxon. However, many Central Asian species previously described by various authors within Geodromicus also belong to the genus Trichodromeus.